L-cysteine mitigates busulfan-induced testicular injury through modulation of CBS/H2S axis - Liu, Song; Wei, Bin; Wei, Han; Xu, Anran; Sheng, Lianbing; Sun, Xiangyang; Dong, Yunling; Yang, Huijun (Frontiers in Cell and Developmental Biology, 2025)
Global male infertility, characterized by decreased spermatogenesis and sperm quality, is a significant concern. L-cysteine, essential for hydrogen sulfide (H2S) synthesis, offers numerous biological advantages. However, the protective mechanisms of L-cysteine in treating spermatogenic dysfunction need further exploration. This study aims to examine L-cysteine’s protective effects on busulfan-induced testicular toxicity. Results show that administering L-cysteine at different doses (2.5, 5.0, and 10 mg/kg) led to notable improvements in final body weight, testis weight, sperm count, sperm motility, testosterone levels, and seminiferous tubule architecture. At a 5.0 mg/kg dosage, L-cysteine mitigated testicular injury by activating the CBS/H2S axis. Moreover, L-cysteine effectively reduced apoptosis and oxidative stress through Nrf2/HO-1 pathway activation. Various analyses demonstrated that L-cysteine enhanced the repair of the blood-testis barrier (BTB) disrupted by busulfan. Mechanistically, L-cysteine activated the PI3K/Akt/mTOR pathway in the testes. Notably, the CBS inhibitor AOAA reversed L-cysteine’s protective effects on busulfan-induced testicular damage. In summary, the study suggests that L-cysteine can safeguard against busulfan-induced spermatogenic dysfunction, apoptosis, oxidative stress, and BTB disruption by modulating the PI3K/Akt/mTOR pathway, hinging on CBS/H2S axis activation. These findings propose L-cysteine as a potential treatment for male infertility, particularly in individuals undergoing busulfan chemotherapy.